Association of Upper Crossed Syndrome with Neck Pain in Lactating Women - Shumayam Shafeeq, Asma Noreen, Zainab Nasrullah, Aleena Masood, Waqar ul Hassan, Shoaib Ahmad, Adnan Hashim, (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Introduction: Physiotherapy benefits women both in the antenatal and postnatal periods. Postnatal education is essential for guiding women about correct breastfeeding positioning. However, studies on the efficacy of this approach in developing countries like Pakistan are limited in the literature. This study is aimed to assess the association of upper crossed syndrome in lactating women. Methods: Descriptive study design was used for this cross-sectional study in which the following inclusion criteria interviewed 141 lactating women of Age 15-47 years. All these women were inpatients in Gynecology Ward at District Head Quarters Hospital, Sheikhupura. The neck disability index, Reedco posture assessment, and Numeric pain rating scale were used for data collection. Data were analyzed using SPSS version 21. The Reedco scale assessed the posture alignment of the head, shoulders, and spine. Results: 53% of the participants were from the 15-25 age group, and the rest were from different age groups ranging from 26-47 years.79.4% had a cesarean section for the birth of their child.80.9% had 1-3 children.58.9% belong to the lower socioeconomic status. When the chi-square test was applied to check the association between all variables, it was evident that the patient's age is significantly associated with Reedco posture assessment and Neck disability index, Mode of delivery with Neck disability index. Still, there is no significant association between age and the Numeric pain rating scale, Birth history with the Numeric pain scale, and Reedco posture assessment. In the end, it was also revealed that Upper crossed syndrome and Neck pain had a statistically significant association of 0.033.(p-value<0.05). This study has potential benefits for the community as it sheds light on an important issue that affects lactating women. By identifying a possible association between upper crossed syndrome and neck pain in lactating women, healthcare professionals can develop more effective treatment plans to alleviate the discomfort experienced by these women. This can lead to an improvement in their overall quality of life and mental health. Conclusion: This study found an association between upper-crossed syndrome and neck pain. It was found that the lactating mothers with upper crossed syndrome were somehow related to bad Posture and suffered from musculoskeletal pain, especially neck pain. A lack of knowledge and awareness about correct positioning during breastfeeding is evidenced in this study. Women were unaware of the importance of physical therapy and the role of it during and after pregnancy. Keywords: Lactation, Neck pain, Kyphosis, Lordosis, over inhibition, Antenatal, Postnatal, Winging of scapula, Posture